MODELLING OF RING-SHAPED ULTRASONIC WAVEGUIDES FOR TESTING OF MECHANICAL PROPERTIES AND THERAPEUTIC TREATMENT OF BIOLOGICAL TISSUES - V. T. Minchenya; D. A. Stepanenko; A. I. Bobrovskaya (Приборы и методы измерений, 2015)
The article presents results of modelling of ring-shaped waveguide tool for ultrasonic treatment of biological materials, particularly malignant tumours, and testing of their mechanical properties. Harmonic analysis of forced flexural vibration of the waveguide using ANSYS software and APDL programming language was implemented for determination of waveguide geometric parameters providing its resonance for the given excitation frequency. The developed finite element model accounts for interaction between the waveguide and tumour tissue as well as initial prestressing of tissue radially compressed by the waveguide. Resonant curves of the waveguide in terms of its thickness and diameter are calculated and presented. Principle of application of the developed modeling technique for extraction of diagnostic data on mechanical properties of biological tissues is described.